A Sequential Three-Stage Integer Goal Programming (IGP) Model for Faculty-Course-Time-Classroom Assignments (Informatica, 2025)
A Sequential Three-Stage Integer Goal Programming (IGP) Model for Faculty-Course-Time-Classroom Assignments